Analysis of the Impact of Community Institutional Strengthening on the Sustainability of the "Spirit of Independence" Farmer Group and the "Industrial Circle" Livestock Group in Uso Village, Banggai Regency - Zulkipli N Salingkat; Budi Santosa (Asian Journal of Social and Humanities, 2023)
The purpose of this research was to analyse the impact of strengthening community institutions on the sustainability of farmer and livestock groups. This included the process of establishing and strengthening community institutions, how the company's strategy in developing governance systems, decision-making mechanisms, system evaluation including community institutional benefits, contributions to SDGs 16 and their relation to ISO 26000. The method of this research used quantitative methods sourced from primary data and secondary data to determine the impact of strengthening community institutions on the sustainability of the Semangat Mandiri farmer group and the Lingkar Industri livestock group located in Uso village, Batui sub-district, Banggai regency, Central Sulawesi province. Data analysis was carried out using triangulation to validate data linkages from field research. Furthermore, an in-depth study of the relationship between the subject and object under study was carried out to explain the formulation of the problem and the purpose of the study and draw conclusions from the research results. The results showed that PT. PAU has a complete commitment in implementing CSR programs. This commitment could be seen from the implementation of community institutional strengthening, aspects of governance systems, decision-making mechanisms, and evaluation of governance systems in achieving ISO 26000 and SDGs 16 in farmer and livestock groups in Uso village, Banggai Regency which have a good impact on the community and the company.